2023
DOI: 10.5433/1679-0359.2023v44n3p1127
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of cultivars and clonal selections of peach rootstocks to excess aluminum

Marcos Vinícius Miranda Aguilar,
Jean Michel Moura-Bueno,
Newton Alex Mayer
et al.

Abstract: Forms of aluminum (Al) present in the solution of tropical and subtropical soils can cause toxicity in rootstocks and peach cultivars, impairing growth and productivity. This can be minimized by growing Al-tolerant rootstocks and cultivars. However, this is not sufficiently known, especially because plant breeding programs do not always consider tolerance as a selection variable for genetic materials. The study aimed to (a) select cultivars and clonal selections of Al-tolerant peach rootstocks, (b) identify va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…As a result, there was also a possible maintained of secondary roots emitted by E. uniflora seedlings in the presence of Al, indicating a root system with greater adaptability to Al stress. Plants without toxic effects of Al on the root system tend to absorb more water and nutrients and consequently contribute to maintained production of root and leaf biomass (Aguilar et al, 2023a), as observed in this experiment (Table 1). This is evidence of the tolerance potential of E. uniflora seedlings to Al stress.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…As a result, there was also a possible maintained of secondary roots emitted by E. uniflora seedlings in the presence of Al, indicating a root system with greater adaptability to Al stress. Plants without toxic effects of Al on the root system tend to absorb more water and nutrients and consequently contribute to maintained production of root and leaf biomass (Aguilar et al, 2023a), as observed in this experiment (Table 1). This is evidence of the tolerance potential of E. uniflora seedlings to Al stress.…”
Section: Resultssupporting
confidence: 59%
“…Aluminum in the solution can impair cell division and elongation, increasing root diameter, decreasing growth and consequently root volume and surface area (Aguilar et al, 2023a). As a result, roots will likely reduce water and nutrient uptake, which may decrease plant growth and biomass production (Mayer & Ueno, 2021).…”
Section: Introductionmentioning
confidence: 99%